2015
DOI: 10.1016/j.cub.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Avidities and Transcriptional Silencing in Yeast

Abstract: A classical example of "transcriptional silencing" is found in the yeast S. cerevisiae mating-type switch [1, 2]. The gene pairs a1/a2 and α1/α2, positioned at the loci HMR and HML, respectively, are silenced by Sir proteins recruited by proteins that bind sites flanking each locus. Transfer of either gene pair to the Sir-free MAT locus, or mutation of the Sirs, allows expression of those genes at levels sufficient to foster yeast mating. Here we confirm that, in the absence of Sirs, a1 and a2 at HMR are expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…A protein complex containing Sir2, Sir3, and Sir4 is recruited to specific sites, known as silencers, by DNA-bound factors and Sir1. The Sir2/3/4 complex interacts with histones and DNA adjacent to silencers, thereby imposing greater nucleosome occupancy and more precise nucleosome positioning across silenced domains (Weiss and Simpson 1998;Ravindra et al 1999;Wang et al 2015). When Sir proteins are reconstituted with chromatin templates in vitro, nucleosomes aggregate; sometimes forming distinctive 20-nm fibers visible by electron microscopy (EM) (Onishi et al 2007;Johnson et al 2009).…”
Section: Distinctive Molecular Features Of Silent Chromatinmentioning
confidence: 99%
“…A protein complex containing Sir2, Sir3, and Sir4 is recruited to specific sites, known as silencers, by DNA-bound factors and Sir1. The Sir2/3/4 complex interacts with histones and DNA adjacent to silencers, thereby imposing greater nucleosome occupancy and more precise nucleosome positioning across silenced domains (Weiss and Simpson 1998;Ravindra et al 1999;Wang et al 2015). When Sir proteins are reconstituted with chromatin templates in vitro, nucleosomes aggregate; sometimes forming distinctive 20-nm fibers visible by electron microscopy (EM) (Onishi et al 2007;Johnson et al 2009).…”
Section: Distinctive Molecular Features Of Silent Chromatinmentioning
confidence: 99%
“…They observed that nucleosome occupancy of the HMR locus, which harbors the cell identity gene pair a1/a2, increased from 30-40% in the absence of Sirs (i.e., in a sir -mutant), to 50-60% in their presence [1]. Importantly, the authors observed this effect under circumstances in which the genes located at HMR were transcriptionally inactive irrespective of the presence of Sirs.…”
Section: Current Biologymentioning
confidence: 93%
“…Over the past two decades, work from a number of laboratories has led to a revision of this 'dark matter' view of heterochromatin. The latest is a paper from Mark Ptashne and colleagues appearing in a recent issue of Current Biology [1]. Using as their model the Sir protein-regulated silent chromatin of the budding yeast Saccharomyces cerevisiae, these authors demonstrate that while Sir-heterochromatin can extinguish expression of weakly activated genes, it becomes increasingly less effective in repressing transcription as the strength of activation is increased.…”
Section: Current Biologymentioning
confidence: 99%
See 2 more Smart Citations